Toward Sustainability: Evaluating ESD Implementation in K-12 Schools: A Systematic Review - Farras Alifa; Sri Rahayu; Oktavia Sulistina; Naif Mastoor Alsulami (J-PEK (Jurnal Pembelajaran Kimia), 2025)
This systematic review evaluates 30 peer-reviewed articles published between 2015 and 2025, using the PRISMA method. The implementation methods are categorized into five groups: Classroom-Based Implementation (n = 10), Project-Based and Experiential Learning (n = 3), Textbook and Curriculum-Based Implementation (n = 3), School Infrastructure and Leadership (n = 3), and Extracurricular and Global Initiatives (n = 11). Classroom-based approaches are the most widely applied, featuring strategies such as transdisciplinary teaching and outdoor learning. A significant barrier identified across the literature is the lack of teacher preparedness and limited access to professional development (reported in 18 studies), alongside challenges such as insufficient institutional backing and resource limitations. This review presents a comprehensive typology of ESD implementation methods in K-12 settings, highlighting underrepresented areas such as leadership and structural integration. Mapping the distribution and frequency of implementation strategies provides a clearer understanding of current practices and gaps. In response, the review proposes actionable recommendations to improve ESD delivery, emphasizing the need for comprehensive teacher training, innovative curriculum approaches, and coordinated efforts across educational and community sectors to foster meaningful and sustainable learning outcomes.